2014
DOI: 10.1080/15475441.2014.896168
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month-Old Infants’ Encoding of Goal and Source Paths in Agentive and Non-Agentive Motion Events

Abstract: Across languages and event types (agentive and non-agentive motion, transfer, change of state, attach/detach), goal paths are privileged over source paths in the linguistic encoding of events. Furthermore, some linguistic analyses suggest that goal paths are more central than source paths in the semantic and syntactic structure of motion verbs. However, in the non-linguistic memory of children and adults, a goal bias shows up only for events involving intentional, goal-directed, action. Three experiments explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 54 publications
7
47
0
Order By: Relevance
“…The measured gaze patterns indicated that, already at 14 months of age, infants were able to segment the continuous action flow into sub-actions, by looking proactively at the goal of each sub-task [i.e., the object to be grasped or the target location of the transport -see also Baldwin et al (2001) with a different methodology]. Recent research by Lakusta and Carey (2014) confirmed the limitation that only when the event involves action of an agent, 12-month-olds will give privilege to its goals. The results are in line with studies on adults suggesting that human action is perceived as hierarchically organized (Zacks and Tversky, 2001) with particular relevance given to action goal.…”
mentioning
confidence: 99%
“…The measured gaze patterns indicated that, already at 14 months of age, infants were able to segment the continuous action flow into sub-actions, by looking proactively at the goal of each sub-task [i.e., the object to be grasped or the target location of the transport -see also Baldwin et al (2001) with a different methodology]. Recent research by Lakusta and Carey (2014) confirmed the limitation that only when the event involves action of an agent, 12-month-olds will give privilege to its goals. The results are in line with studies on adults suggesting that human action is perceived as hierarchically organized (Zacks and Tversky, 2001) with particular relevance given to action goal.…”
mentioning
confidence: 99%
“…By 14 months infants discriminate via paths (over vs. under) (e.g., Pulverman, et al, 2008; Pulverman et al 2013) and by 10 months they can detect an invariant via path (Pruden, Roseberry, Goksun, Hirsh-Pasek, & Golinkoff, 2013; also see Konishi, Pruden, Golinkoff and Hirsh-Pasek, 2014 for an extension of these results). By 12 months infants encode goal and source paths (e.g., into a bowl vs. onto a box; out of a bowl vs. off of a box) (Lakusta, Wagner, O-Hearn, & Landau, 2007; Reardon, Lakusta, Muentener, & Carey, 2009; Wagner, 2009; Lakusta & Carey, 2015). In these latter studies 12-month-old infants were familiarized to a figure (animate-like, stuffed duck/agentive balloon) moving to one of two goal objects (e.g., into a bowl vs. onto a block).…”
Section: 0 Introductionmentioning
confidence: 99%
“…This suggests that, during familiarization, infants attended to and represented the goal path in these motion events, and during test they were more surprised when the figure moved to a different goal. Further findings suggested that when the source objects were made sufficiently ‘salient’ (relatively large in size and multicolored) infants also represent the source path; and they preferentially attend to the goal over the (salient) source when the two were pitted up against each other (Lakusta et al, 2007; Lakusta & Carey, 2015). …”
Section: 0 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ikegami 1987;Ihara and Fuijita 2000;Stefanowitsch and Rohde 2004;Lakusta and Landau 2005;Papafragou 2010; Lakusta and Landau 2012;Lakusta and Carey 2014). In most studies, the wheel shows a clear preference and spins towards the Goal.…”
Section: Introductionmentioning
confidence: 99%